2022
DOI: 10.1038/s41594-022-00859-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of inactive-state GPCRs with a universal nanobody

Abstract: Cryogenic electron microscopy (cryo-EM) has widened the field of structure-based drug discovery by allowing for routine determination of membrane protein structures previously intractable. However, despite representing one of the largest classes of therapeutic targets, most inactive-state G protein-coupled receptors (GPCRs) have remained .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…31,32 For SST 2 , recent structures obtained by cryo-electron microscopy for the inactive (apo-) receptor and the G-protein/octreotide-bound receptor suggest a similar phenomenon. 33,34 In line with this, the addition of GTP or GppNHp or pertussis toxin to membrane preparations of SST 2 -synthesizing cells led to a marked reduction in the binding affinity of different radiolabeled agonists. 35−37 Consequently, as the GTP/GDP level might be lower in cell homogenates, the G-protein bound receptor state and thus agonist binding should actually be favored.…”
Section: T H Imentioning
confidence: 67%
See 1 more Smart Citation
“…31,32 For SST 2 , recent structures obtained by cryo-electron microscopy for the inactive (apo-) receptor and the G-protein/octreotide-bound receptor suggest a similar phenomenon. 33,34 In line with this, the addition of GTP or GppNHp or pertussis toxin to membrane preparations of SST 2 -synthesizing cells led to a marked reduction in the binding affinity of different radiolabeled agonists. 35−37 Consequently, as the GTP/GDP level might be lower in cell homogenates, the G-protein bound receptor state and thus agonist binding should actually be favored.…”
Section: T H Imentioning
confidence: 67%
“…A striking example for this can be found in a study of Florio and Sternweis, who observed a dramatic increase in binding potency of the agonist oxotremorine to muscarinic receptors in the presence of the G-protein G 0 . For adenosine A 2A and β 1 -adrenoreceptors, it has been shown that the preference for the G-protein coupled receptor originates on a molecular basis from a narrower binding pocket and tighter contacts to the ligand upon G-protein binding. , For SST 2 , recent structures obtained by cryo-electron microscopy for the inactive (apo-) receptor and the G-protein/octreotide-bound receptor suggest a similar phenomenon. , In line with this, the addition of GTP or GppNHp or pertussis toxin to membrane preparations of SST 2 -synthesizing cells led to a marked reduction in the binding affinity of different radiolabeled agonists. Consequently, as the GTP/GDP level might be lower in cell homogenates, the G-protein bound receptor state and thus agonist binding should actually be favored. In accordance with this consideration, Koenig et al characterized Neuro2A neuroblastoma cells regarding the binding of the selective SST 2 agonist [ 125 I]-BIM-23027 (c­[N-Me-Ala-Tyr-D-Trp-Lys-Abu-Phe]) but were not able to determine both K d and B max values when using intact cells, which was related by the authors to high nonspecific binding but also the presence of a high GTP concentration in the cells.…”
Section: Resultsmentioning
confidence: 97%
“…These include two structures in complex with antagonists β-funaltrexamine (β-FNA) (PDB ID: 4DKL) [ 21 ] and alvimopan (PDB ID: 7UL4) [ 38 ]; five structures in complex with partial agonists PZM21 (PDB ID: 7SBF, 8EFO) [ 39 , 40 ], FH210 (PDB ID: 7SCG) [ 39 ], oliceridine (TRV130) (PDB ID: 8EFB) [ 40 ], and SR17018 (PDB ID: 8EFL) [ 40 ]; and six structures bound with full agonists BU72 (PDB ID: 5C1M) [ 41 ], [D-Ala2, N-MePhe4, Gly-ol5] enkephalin (DAMGO, a synthetic peptide) (PDB ID: 6DDE, 6DDF, and 8EFQ) [ 40 , 42 ], fentanyl (PDB ID: 8EF5) [ 40 ], morphine (PDB ID:8EF6) [ 40 ], lofentanil (PDB ID: 7T2H) [ 43 ], and mitragynine pseudoindoxyl (PDB ID: 7T2G) [ 43 ]. Another recently solved structure is bound with a bitopic ligand (PDB ID: 7U2L) [ 8 ].…”
Section: Structures Of μ Opioid Receptor (Mor)mentioning
confidence: 99%
“…We anticipate that these tagging sites can also be transferred to other nanobodies, such as Nb6, which has recently been introduced as a universal tool to determine the structures of many different GPCRs in their inactive state. 47 A further option may be to derive the PCS tensors from the nanobody resonances, instead of the GPCR resonances, with the goal that the tensors could be used universally for various recognized proteins. However, this approach may suffer from extensive line broadening due to PREs (paramagnetic relaxation enhancements) as well as from additional mobility between the nanobody and the recognized protein.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%